Optimization Of Biosorption Conditions For Crude Oil Spills Using Acetylated And Unacetylated Biosorbents Derived From Cissus Populnea Leaves Stem And Roots - Joel Tari Honda; J. M. Yelwa; Aeneas N. Ulteino; S. Abudllahi; Umar, A. S; Husaina G. Anchau; Kalu Michael Kalu (International Journal of Science and Environment (IJSE), 2023)
The biosorption of crude-oil spill using acetylated and unacetylated Cissus populnea leave, stem and root biosorbents was investigated in this study. The acetylated and unacetylated biosorbents was characterized by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The FTIR spectra confirmed the formation of the acetyl group while SEM morphological analysis of acetylated biosorbent showed rough macrostructure surfaces with large hollows between the strand. The effectiveness of the biosorbents was evaluated based on their ability to remove crude oil from an aqueous solution. The results sho wed that the acetylated biosorbents had higher oil sorption capacities compared to the unacetylated biosorbents. The highest oil sorption capacity was observed for the acetylated stem biosorbent, which had a sorption capacity of 30.09 g/g. The unacetylated leaves biosorbent had the lowest oil sorption capacity, with a sorption capacity of 20.4 g/g. The leaves and roots biosorbents showed intermediate oil sorption capacities. The study also showed that the biosorption capacity of the biosorbents increased with increasing initial oil concentration and contact time, while decreasing with increasing biosorbent particle size. The results suggest that acetylated Cissus populnea biosorbents have potential as an effective and low-cost alternative for the remediation of crude-oil spills.